Mental Readiness of Residents Refusing Assistance to Face Social Stigma Ahead of Reintegration Period at Boyolali Prison - Sartika Girsang; Jusuf Tjahjo Purnomo (Universitas PGRI Yogyakarta, 2026)
This study explores the mental preparedness of prisoners to cope with social stigma as they approach reintegration into society in Indonesia. Its significance lies in its examination of the complex interplay between psychological well-being and external social pressures within the Indonesian correctional landscape. This topic has not been thoroughly explored in previous research. Using a qualitative phenomenological approach, this study examines the subjective experiences of prisoners approaching release, providing valuable insights into their emotion regulation and coping strategies. Data were collected through semi-structured interviews, observation, and documentation, followed by thematic analysis facilitated by MAXQDA software. This software was crucial for organizing the qualitative data, allowing for the systematic exploration of themes that enriched the phenomenological analysis. The findings revealed that participants experienced significant impacts from social stigma, manifesting as feelings of shame and anxiety regarding social acceptance. However, they also demonstrated adaptive coping strategies, emphasizing the role of emotion regulation and social support in enhancing their mental preparedness for reintegration. This study provides new insights into the crucial factors influencing prisoners' readiness for reintegration, highlighting the dual influence of internal psychological resilience and external social perceptions. In contrast to previous research, this study specifically addresses the importance of mental preparedness in mitigating the negative impacts of stigma. It outlines actionable strategies to support successful reintegration efforts within the correctional system. Keywords: mental readiness, social stigma, reintegration